Cost-effectiveness analysis of transcatheter aortic valve implantation versus surgical aortic valve replacement in patients with severe aortic stenosis at low risk of surgical mortality in Sweden - Konrad Nilsson; Stefan James; Oskar Angerås; Jenny Backes; Henrik Bjursten; Pascal Candolfi; Mattias Götberg; Henrik Hagström; Chiara Malmberg; Niels Erik Nielsen; Archita Sarmah; Magnus Settergren; et al. (Upsala Journal of Medical Sciences)
Background: Transcatheter aortic valve implantation (TAVI) has shown similar or improved clinical outcomes compared with surgical aortic valve replacement (SAVR) in patients with symptomatic severe aortic stenosis at low risk for surgical mortality. This cost-utility analysis compared TAVI with SAPIEN 3 versus SAVR in symptomatic severe aortic stenosis patients at low risk of surgical mortality from the perspective of the Swedish healthcare system. Methods: A published, two-stage, Markov-based cost-utility model that captured clinical outcomes from the Swedish Web-system for Enhancement and Development of Evidence-based care in Heart disease Evaluated according to Recommended Therapies (SWEDEHEART) registry (2018–2020) was adapted from the perspective of the Swedish healthcare system using local general population mortality, utility and costs data. The model had a lifetime horizon. Model outputs included changes in direct healthcare costs and health-related quality of life from using TAVI as compared with SAVR. Results: TAVI with SAPIEN 3 resulted in lifetime costs per patient of 484,142 SEK Swedish krona (SEK) and lifetime quality-adjusted life years (QALYs) per patient of 7.16, whilst SAVR resulted in lifetime costs and QALYs per patient of 457,625 SEK and 6.81 QALYs, respectively. Compared with SAVR, TAVI offered an incremental improvement of +0.35 QALY per patient at an increased cost of +26,517 SEK per patient over a lifetime horizon, resulting in an incremental cost-effectiveness ratio of 76,532 SEK per QALY gained. Conclusion: TAVI with SAPIEN 3 is a cost-effective option versus SAVR for patients with symptomatic severe aortic stenosis at low risk for surgical mortality treated in the Swedish healthcare setting. These findings may inform policy decisions in Sweden for the management of this patient group.